Recognition of the genera Igutettix Matsumura and Vilbasteana Anufriev (Hemiptera: Cicadellidae: Typhlocybinae), with discovery of a new related genus from Japan - Ohara, Naomichi; Hayashi, Masami (Zootaxa, 2022)
The dikraneurine genus Igutettix Matsumura and its allies are revised. The definition of Igutettix is corrected and newly proposed on the basis of the true I. pulverosus Matsumura, resurrected from the synonymy with Dikraneura oculata Lindberg. Accordingly, the genus Vilbasteana Anufriev established for the latter species is resurrected as an independent valid genus. The genera Vikabara Dworakowska and Paraafrakra Chiang, Hsu et Knight, are newly synonymized under Igutettix and Vilbasteana, respectively. Igutettix is composed of three species, I. pulverosus Matsumura sp. rev., I. ater (Dworakowska) comb. nov. and I. glossatus (Dworakowska) comb. nov. Vilbasteana comprises two species, V. oculata (Lindberg) comb. rev. and V. fulva (Chiang, Hsu et Knight) comb. nov. Furthermore, a new genus, Cornicola gen. nov. related to Igutettix is described for a new species C. mizuki sp. nov. from Japan.